Pelatihan Public Speaking Mahasiswa Desain Komunikasi Visual 2022 Fakultas Seni dan Desain UNM - Fadhillah S, Nurul; Siti Syarifah Wafiqah Wardah (Jurusan Teknik Informatika dan Komputer, 2023)
This community service activity is in the form of public speaking training which targets students of the Visual Communication Design Study Program (DKV), class of 2022, Department of Fine Arts and Design, Faculty of Art and Design (FSD), Makassar State University as participants. In total there were 193 participants divided into 5 different classes. The purpose of this service is to improve soft skill DKV student communication through training in public speaking, while at the same time providing an understanding that DKV students do not only have to focus on tools but also must be strengthened by the ability to communicate. The location of this service is held in the DJ 101 A, B and C rooms of the Faculty of Art and Design. The method used is to give lectures at the first meeting, then in the second week the participants do public speaking by answering pre-selected questions and continuing with the presentation of the work. The results of this community service activity are measured by distributing questionnaires online to students and shows that both the knowledge and skills of DKV students are related to public speaking already increasing.